Time and Frequency Analysis of EMG Signals for Simultaneous Evaluation of Knee Muscles in Concentric and Eccentric Strength Training in Healthy Men - Mehdi Zeygham Jahani; Ali Yaghoubi; Mohamad Amin Younessi Heravi (Shiraz University of Medical Sciences, 2022)
Background: Strength training has been a common intervention used to improve neuromuscular activity within the synergic and/or agonist-antagonist muscles. This study aimed to evaluate simultaneous electrical activity of quadriceps and hamstring muscles after strength eccentric training versus concentric training.Methods: This experimental study has a between-group comparison design with a population of 26 males divided into two groups, namely the eccentric training group and the concentric training group. Maximal knee extension force and bipolar surface electromyography (EMG) signals from quadriceps and hamstring muscles were simultaneously recorded pre- and post-concentric and eccentric strength training. After EMG pre-processing for noise reduction, EMG signals were evaluated in two groups by time and frequency analysis. Nine EMG features (six time features and three frequency features) were analyzed in two groups pre- and post-training by statistical analysis.Results: The results showed that the maximal voluntary isometric contraction (MIVC) of quadriceps muscles was significantly increased in both groups from pre- to post-training (p <0.05). Moreover, eccentric training resulted in greater increases in time features of EMG for quadriceps and hamstring muscles compared to concentric training (p <0.05). All frequency features showed significant changes in pre- and post-tests for the eccentric training group (p <0.05); however, no significant difference was observed in the frequency features in the post-test compared to the pre-test in the concentric training group (p >0.05).Conclusion: Based on the current results, great changes in time and frequency features of quadriceps and hamstring EMGs were achieved using eccentric training. Thus, eccentric strength training could be more effective in triggering neuromuscular activity within the agonist and antagonist muscles simultaneously.